2018
DOI: 10.1002/14651858.cd013016
|View full text |Cite
|
Sign up to set email alerts
|

Real-time polymerase chain reaction tests versus antenatal culture tests for the screening of maternal group B Streptococcus colonisation in labour

Abstract: Sian (2018) Realtime polymerase chain reaction tests versus antenatal culture tests for the screening of maternal group B Streptococcus colonisation in labour. Cochrane Database of Systematic Reviews, 2018 (5). CD013016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…However, it may be challenging to quantify certain factors (eg increased stigma) and draw direct comparisons between the benefits and harms (eg reduced transmission versus false-positive results). Evaluating the potential benefits and harms of ACF may be even more challenging in low- and middle-income settings, as many do not have established processes for the development of screening policies in place [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may be challenging to quantify certain factors (eg increased stigma) and draw direct comparisons between the benefits and harms (eg reduced transmission versus false-positive results). Evaluating the potential benefits and harms of ACF may be even more challenging in low- and middle-income settings, as many do not have established processes for the development of screening policies in place [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…As with the review by Seedat et al ( 14 ) of population-based screening criteria adopted across a number of countries, the findings of the workshop were more likely to focus on considerations relating to “the screening program” as opposed to the condition, test, and treatment. The issues identified in relation to the screening program were largely those that would be relevant to all screening programs, not only preconception expanded carrier screening.…”
Section: Discussionmentioning
confidence: 99%
“…While the Wilson and Jungner principles are the benchmark for government decision-making in screening, the ways in which they have been applied in practice vary across the globe. This is highlighted through a recent review of the criteria for deciding whether to introduce screening programs in Australia, Canada, Denmark, Finland, France, Germany, Italy, the Netherlands, New Zealand, Sweden, the UK, and the USA ( 14 ). Across these countries, Seedat et al ( 14 ) identified 46 unique criteria that were associated with screening in general, most of which related to the screening program (27) as opposed to the condition (7), test (6), and treatment (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the practical implementation of population screening creates further potential obstacles to establishing that the benefits thereof outweigh the harms, as the improper implementation thereof can negate the anticipated benefits [ 18 ]. Economic factors can also be relevant to the implementation of a population screening programme.…”
Section: Introductionmentioning
confidence: 99%